Improving Village Entrepreneurship Through The Role Of The Mudharabah Agreement - Iskandar, Iskandar; Arifudin, Opan; Karmawan, Slamet (International Journal of Science Education and Technology Management, 2025)
This research is motivated by the fact that every entrepreneurial development experience capital difficulty. Capital loan transactions, sharia principles can influence business development. The aim of the research is to determine the role of Mudharabah in developing entrepreneurship in villages and introducing more deeply about sharia contracts, namely contracts Mudharabah. This research uses a qualitative method with a descriptive approach. The results of this research indicate that the role of contracts Mudharabah This has a lot of influence on the development of entrepreneurship in the village so that of course entrepreneurs who want to develop a business but cannot because of limited capital, the role of this mudharabah agreement can help to develop their business into a large business. This mudharabah financing is required to be expanded further in the surrounding community so that many people are familiar with this mudharabah financing. Socialization regarding mudharabah contracts must continue to be carried out and implemented in communities that primarily do not have capital to run their businesses. So, this contract is used as a capital solution.